Differential Influence of Life Cycle on Growth and Toxin Production of three Pseudo‐nitzschia Species (Bacillariophyceae). Issue 5 (24th August 2019) - Sauvey, Aurore; Claquin, Pascal; Le Roy, Bertrand; Le Gac, Mickael; Fauchot, Juliette
Abstract : We used a multistrain approach to study the intra‐ and interspecific variability of the growth rates of three Pseudo‐nitzschia species – P. australis, P. fraudulenta, and P. pungens – and of their domoic acid (DA) production. We carried out mating and batch experiments to investigate the respective effects of strain age and cell size, and thus the influence of their life cycle on the physiology of these species. The cell size – life cycle relationship was characteristic of each species. The influence of age and cell size on the intraspecific variability of growth rates suggests that these characteristics should be considered cautiously for the strains used in physiological studies on Pseudo‐nitzschia species. The results from all three species do not support the hypothesis of a decrease in DA production with time since isolation from natural populations. In P. australis, the cellular DA content was rather a function of cell size. More particularly, cells at the gametangia stage of their life cycle contained up to six times more DA than smaller or larger cells incapable of sexual reproduction. These findings reveal a link between P. australis life cycle and cell toxicity. This suggest that life cycle dynamics in Pseudo‐nitzschia natural populations may influence bloom toxicity.